Workforce Economics in Hospitality: Analyzing the Determinants of Employee Performance at Sumberkima Hill Hotel - Adnyaswari, Ni Putu; Irwansyah, Rudi; Trianasari, Trianasari (International Journal of Economics Development Research (IJEDR), 2025)
Employee performance plays a vital role in shaping a hotel's reputation and ensuring high-quality guest experiences, especially in a competitive tourism landscape like Bali. Preliminary observations at several hotels in West Bali, including Sumberkima Hill Hotel, revealed performance-related challenges among staff. This study aims to analyze the economic and organizational determinants that influence employee performance, focusing on five key variables: ability, motivation, work environment, leadership, and organizational culture. Adopting a causal quantitative research design, data were collected from 120 respondents using questionnaires based on a 5-point Likert scale. The data were analyzed using multiple linear regression along with F-tests, t-tests, and the coefficient of determination (R²), processed via SPSS. Results indicate that all five variables have a positive and significant effect on employee performance at Sumberkima Hill Hotel. These findings highlight the importance of investing in workforce development as an economic strategy for enhancing service quality in the hospitality sector. As competition intensifies in the post-pandemic era, understanding the economic dynamics of employee performance becomes essential for hotel sustainability and growth.